1995
DOI: 10.1016/0896-6273(95)90276-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions of S4 voltage sensor in shaker K+ channel

Abstract: The S4 segment comprises part of the voltage sensor in Shaker K+ channels. We have used a strategy similar to intragenic suppression, but without a genetic selection, to identify electrostatic interactions of the S4 segment that may be important in the mechanism of voltage-dependent activation. The S4 neutralization mutations K374Q and R377Q block maturation of the protein, suggesting that they prevent proper folding. K374Q is specifically and efficiently rescued by the second site mutations E293Q and D316N, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
404
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(438 citation statements)
references
References 50 publications
33
404
0
1
Order By: Relevance
“…The eag constraint was not included, however. Two possible packing arrangements of S2, S3, and S4 were obtained that are consistent with second-site suppressor results in Shaker, suggesting that E283 in S2 interacts with R368 and R371 in S4, and K374 in S4 interacts with E293 in S2 and D316 in S3 (22,23,30). Identification of the ion-binding site in eag provides an additional structural constraint between S2 and S3 (6), and strong experimental justification now has been provided for use of Shaker and eag constraints in the same model.…”
Section: Model For Structural Rearrangements Underlying Two Stages Ofsupporting
confidence: 61%
See 1 more Smart Citation
“…The eag constraint was not included, however. Two possible packing arrangements of S2, S3, and S4 were obtained that are consistent with second-site suppressor results in Shaker, suggesting that E283 in S2 interacts with R368 and R371 in S4, and K374 in S4 interacts with E293 in S2 and D316 in S3 (22,23,30). Identification of the ion-binding site in eag provides an additional structural constraint between S2 and S3 (6), and strong experimental justification now has been provided for use of Shaker and eag constraints in the same model.…”
Section: Model For Structural Rearrangements Underlying Two Stages Ofsupporting
confidence: 61%
“…Evidence for conservation of key molecular details in the mechanism of voltage-dependent activation in eag and Shaker, two divergent members of the K ϩ channel superfamily, confirms that their voltage sensors share a common structure. Although a detailed atomic structure of a voltage-gated K ϩ channel is not yet available, data from second-site suppressor analysis of Shaker and identification of the ion-binding site in eag put specific constraints on the structural organization of the voltage sensor (6,22,23,30). We previously suggested that these constraints uniquely specify the packing of S2, S3, and S4 in the voltage sensor (6).…”
Section: Model For Structural Rearrangements Underlying Two Stages Ofmentioning
confidence: 99%
“…Our results do not preclude crucial side chain interactions between a small subset of residues in the paddle and other parts of the voltage sensor. The charge carrying Arg residues, for example, are thought to interact with acidic residues in S2 and S3 28,45 , and there appears to be specificity in the positions in S4 where charged moieties contribute to the total gating charge 17 . The Arg residues are the most conserved positions in our paddle constructs, so important interactions involving these residues are fully compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…While many factors are important for normal protein structure, the fact that the L1433K/E mutations affect inactivation similarly excludes the possibility that L1433R alters channel packing by forming additional salt bridges with adjacent acidic amino acids. This also excludes the possibility that addition of a charge to residue 1433 directly involves the electrostatic network inside the protein, which is thought to be important in maintaining the structure of Shaker potassium channels (Papazian et al, 1995). A possible mechanism by which L1433K/E mutations affect inactivation is the disruption ofa hydrophobic interaction with residues of D4/$4.…”
Section: L1433r and R1448c Mutations Affect Hskm1 Inactivation Differmentioning
confidence: 99%